The willingness to perform first aid among high school students and associated factors in Hue, Vietnam - Le Duc Huy; Pham Thanh Tung; Le Nguyen Quynh Nhu; Nguyen Tuan Linh; Dinh Thanh Tra; Nguyen Vu Phuong Thao; Tran Xuan Tien; Hoang Huu Hai; Vo Van Khoa; Nguyen Thi Anh Phuong; Hoang Bao Long; Bui Phuong Linh (PLoS ONE, 2022)
Background Adolescents who are willing to perform first aid can help prevent injuries and ultimately death among themselves and others involved in accidents or injuries. This study aims to estimate the prevalence of students’ willingness to perform first aid procedures and additionally examine associated factors among high school students in Hue, Vietnam. Methods A cross-sectional study utilizing multi-stage stratified random sampling was conducted between April to July 2020 by investigating 798 high school students in Hue, Vietnam. Participants were invited to complete a self-reported questionnaire pertaining to individual demographic characteristics, personal perception of self-efficacy, and willingness to perform first aid. To better interpret these findings, both multivariable linear and Poisson regression models were fitted to evaluate the association between individual student characteristics and the willingness to perform first aid. Results The prevalence of having willingness to perform first aid (defined as ≥4 points out of 5 to all three questions) was 49.9% (95%CI:28.6–71.2%). The major reported barriers in performing first aid were fear of making mistakes and hurting victims (34.4%, 95%CI:31.9–37.0%), no prior first aid training (29.8%, 95%CI:25.9–33.9%), and forgetting first aid steps (23.0%, 95%CI:15.8–32.2%). By employing the multivariable linear regression model, it was identified that students with high (β = 0.614, 95%CI:0.009–1.219) or very high (β = 1.64, 95%CI:0.857–2.422) levels of self-efficacy appeared to be more willing to perform first aid. Similarly, in the Poisson regression models, compared to neutral students, students who reported high (PR = 1.214, 95%CI:1.048–1.407) or very high (PR = 1.871, 95%CI:1.049–3.337) levels of self-efficacy were more willing to perform first aid. Conclusions The level of willingness to perform first aid among high school students in this study population was found to be moderate. Therefore, integrating activities to promote self-efficacy in first aid training could be considered a progressive step towards improving a student’s willingness to provide such life-saving procedures.